The perspectives on fat taxation in Lithuania: theoretical aspect - Gintarė Giriūnienė (Business: Theory and Practice, 2012)
The scientific article analyzes the fat tax and perspectives of its application in Lithuania, because the problem of increasing obesity index has been encountered in the world. Recently the introduction of such tax has caused numerous discussions on the international level, and thus resulted in appearance of new researches. The fundamental methods of how to calculate and assess the tax were determined. One of the main methods is the taxation of smokers or obese persons, which is applied in several states of the USA at present. However, the discriminating features of the fat tax result in linking of such taxation to certain commodities or products, which contain more saturated fats or salt and sugar. The taxation practice of such character has been present in the European countries already. Thus, in this scientific article the research was done in order to learn the perspectives of fat tax in Lithuania using the analysis of statistical data and theoretical survey of assessment of taxation effectiveness for this purpose.